The green bicycle - Al-Mansour, Haifaa 1974- (Dial Books for Young Readers, 2015)
"Since girls do not ride bikes in Riyadh, Saudi Arabia, eleven year old Wadjda has to scheme to get her own"...
Auf dem Schutzumschlag: Based on the award-winning film "Wadjda"
Keywords: JUVENILE FICTION / People & Places / Middle East; JUVENILE FICTION / Girls & Women; JUVENILE FICTION / Family / Alternative Family; Sex role; Coming of age; Bicycles and bicycling; Soziale Probleme; Fahrrad; Mädchen; Freundschaft; Junge; Wunsch; Naher Osten; Saudi Arabia; Riad; Jugendbuch